2018
DOI: 10.1139/cjb-2017-0162
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative potential of the soil seed bank along an elevation gradient of rupestrian grassland in southeastern Brazil

Abstract: The objective of this study was to determine the species richness and abundance of the seed bank and the influence of soil attributes along an elevation gradient (800–1400 m a.s.l.). We examined the floristic similarity among areas and determined the regional diversity along this gradient in Serra do Cipó (Minas Gerais, Brazil). A total of 1975 individuals from 149 species were germinated. Richness and abundance were not linearly related to elevation, and exhibited a threshold at 1200 m. The low degree of simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
0
9
0
5
Order By: Relevance
“…In a study in southeastern Brazil, Saito, Soininen, Fonseca‐Gessner and Siqueira () suggest that a decrease in similarity among communities may be due to a historical imprint caused by dispersal limitation over time instead of to closely related species having similar niches. Thus, the dispersal ability of species and their local abiotic conditions can act as filters, leading to differences in species composition between areas and increasing turnover along the studied gradient (da Luz et al., ). The high number of endemisms at Serra do Cipó may explain the turnover of species.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in southeastern Brazil, Saito, Soininen, Fonseca‐Gessner and Siqueira () suggest that a decrease in similarity among communities may be due to a historical imprint caused by dispersal limitation over time instead of to closely related species having similar niches. Thus, the dispersal ability of species and their local abiotic conditions can act as filters, leading to differences in species composition between areas and increasing turnover along the studied gradient (da Luz et al., ). The high number of endemisms at Serra do Cipó may explain the turnover of species.…”
Section: Discussionmentioning
confidence: 99%
“…Although the studied areas are located within the Cerrado, the very distinct rock parent material provided opportunities for a very distinct flora (Colli‐Silva, Vasconcelos, & Pirani, ; Silveira et al, ). Campos rupestres are known for their high plant species diversity (Alves & Kolbek, ; Le Stradic, Buisson, & Fernandes, ), which is strongly related to substrate heterogeneity (Luz et al, ; Negreiros, Le Stradic, Fernandes, & Rennó, ; Teodoro et al, ). The rock parent material is extremely nutrient poor, leading to nutrient‐impoverished soils, with acidic pH, high aluminium (Al) concentrations and low magnesium (Mg) and calcium (Ca) concentrations (Benites et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Our results suggested that both SB patterns (H′, R, and E′) were highly affected at higher altitudes than the lower altitudes because, at higher elevations, temperature, wind, and soil instability may limit plant growth (Shaheen et al 2015;da Luz et al 2017). Furthermore, more various types of seeds may be correlated with the density of the aboveground vegetation which existed in the lower altitudes (Cheng et al 2001;Valko et al 2014).…”
Section: Status Of Soil Seed Densitymentioning
confidence: 65%